Síndrome de Burnout en monitores que actúan en una fundación de protección especial (2008)
The aim of this study is to evaluate the Burnout syndrome in monitors that act in a foundation of special protection. It also tried to identify associations of burnout dimensions with demographic, professional and psychosocial variables. The MBI- Maslach Burnout Inventory and a questionnaire specially designed for this study and other variables were used as a research tool. The sample was made up of 37 monitors and a protection foundation. Results obtained through the test of t de student, Anova and the correlation of Pearson reveal that the Burnout dimension is associated with the amount of hours spent, the experience in the position and in the place, the thoughts of giving up the profession, job satisfaction, and the perception of how stressful the profession is. Key words: Burnout, job-related stress.